Crack resistance enhancement of gradient bias TiN/Ti multilayer coating by Ti sputtering. (2nd November 2021) - Fang, Zhihao; He, WeiFeng; Chen, Jiao; Sun, Danyang; He, Guangyu
ABSTRACT: In this study, monolayer TiN and multilayer TiN/Ti coatings involving different modulation ratios were deposited on Ti–6Al–4V substrate. Ti interlayers in the multilayer TiN/Ti coatings were prepared under gradient negative bias of –800, –600, and –400 V, with corresponding durations of 2, 2, and 1 min. Mechanical properties and crack' s resistance of the coatings were explored. Damage morphology of coating cross-section was characterized by the focused ion beam (FIB) method. Finite element modelling was used to analyse the stress field. Multilayer TiN/Ti coatings show better impact resistance than monolayer TiN coating. Tensile stress decrease with the increase of interfaces. Gradient bias Ti interlayers restrain crack propagation by cracks deflection and branch. Erosion resistance was evaluated by sand erosion test. Crack propagation and connection account for the coatings failure: the deeper the crack propagation, the higher the erosion rate.